Singlet Exciton Diffusion in Vacuum‐Evaporated Films of Amine‐Based Materials as Studied by Photocurrent and Photoluminescence Quenching Methods. Issue 8 (25th May 2018) - Pelczarski, Daniel; Grygiel, Piotr; Stampor, Waldemar
Abstract : The singlet exciton diffusion lengths are determined by the photoconductivity as well as the luminescence surface quenching technique, in vacuum‐evaporated layers of (4, 4′, 4″‐tris(N‐(3‐methylphenyl)‐N‐phenylylamino) triphenylamine) (m‐MTDATA), 4, 4′, 4″‐tris[2‐naphthyl(phenyl)amino] triphenylamine (2TNATA), and N, N′‐diphenyl‐N, N′‐bis(3‐methylphenyl)‐[1, 1′‐biphenyl]‐4, 4′‐diamine (TPD) which are frequently used for fabrication of electroluminescent and photovoltaic devices. The values are found to be as high as (30 ± 10) nm in 2TNATA and m‐MTDATA, as well as (46 ± 9) nm in TPD films. The corresponding singlet diffusion coefficients of the range between 1 × 10 −3 and 1 × 10 −2 cm 2 s −1, according to a comprehensive study undertaken, are assigned to a sizable electronic coupling induced by strong interactions of intra‐ and inter‐molecular origin in the investigated materials. Abstract : The path length for singlet exciton diffusion is determined in vacuum‐evaporated layers of amine‐based materials, commonly used in organic light emitting diodes and solar cells, by photocurrent and fluorescence quenching methods. Both methods give consistent results. The relatively high value of the singlet diffusion coefficient (10 −3 − 10 −2 cm 2 s −1 ) is assigned to sizable electronic coupling of inter‐ and intra‐molecular origin in this type of solids.